The Aesthetics of Striped Design Motifs and Market Demand on the Songket Tenggarung as the Malay Royal Ceremonial Attire - Muhamad Amin, MOHD JAMIL BIN MUHAMAD AMIN; Arba’iyah Ab. Aziz,; Nor Azlin Hamidon,; Nabilah Mudzafar,; Inda Murni Hairul Anuar, (Research in Management of Technology and Business, 2024)
Textiles have become a very prominent material culture in the Malay world since the early stages of history. Malay traditional textiles show the high achievement of Malay development in aspects of civilization, material culture, customs, art, history, culture, and heritage. Many of the Malay traditional textiles had internal and external influences through maritime and trade relationships. The Songket Tenggarung is one of the Malay traditional textiles produced by the Malay weavers, and it shows many aspects of the aesthetics and beauty of Malay world textiles. Nowadays, many youngsters lack knowledge about Songket, especially Songket Tenggarung. On the other hand, market demand for Malay Songket is getting worse, which is affecting Malay traditional textile production. The purpose of this research is to study the aesthetic elements of Songket Tenggarung striped design motifs on Malay royal ceremonial attire. The qualitative method is implemented to gather research data and findings from observation of the Malay royal ceremonial costumes worn by the Malay royalty and nobles. The aesthetics theory of Zakaria Ali is used by researchers to analyze the design and motifs of Songket Tenggarung. This research signified the beauty of the Songket Tenggarung from an aesthetic point of view. The aims of the study also to give the public a better understanding of the beauty of Songket Tenggarung as Malay traditional textile art and heritage. While this research also gives more knowledge about the textiles of the Malay world in terms of the material culture of Malays.